Problems, Challenges, Dynamics and Supervision Innovation on Nonformal Education In Indonesia - Alim Harun Pamungkas (Universitas Negeri Padang, 2023)
The dynamics of non-formal education supervision in Indonesia and other developing countries involve various institutions, stakeholders and policy changes that can affect its implementation. Innovations in non-formal education supervision, such as the use of technology, community involvement and participatory approaches, can help improve the effectiveness of non-formal education supervision. In its implementation, challenges and problems in non-formal education supervision include limited resources, the diversity of non-formal education institutions, changes in policies and regulations, and community understanding and concern that need to be overcome. Solutions to overcome the challenges of non-formal education supervision involve improving the competence of supervisors, optimizing existing resources, involving the community, adapting changes in policies and regulations, and cooperation between supervision agencies, non-formal education institutions, government and related stakeholders.